The Pediatric Obsessive Compulsive Disorder Treatment Study for Young Children (POTS jr): Developmental Considerations in the Rationale, Design, and Methods - Freeman, Jennifer (2012)
This paper presents the rationale, design, and methods of the Pediatric Obsessive Compulsive Disorder (OCD) Treatment Study for young children (POTS Jr). The study is a multi-site randomized controlled trial (RCT) of family-based Cognitive Behavioral Treatment (CBT) vs. family-based Relaxation Therapy (RT) for young children (ages 5–8) with OCD, which examines the effect of treatment on symptom reduction, functional impairment, and quality of life. Secondary aims evaluate: potential moderators and mediators of treatment response, differences in time course of response, retention rates, and maintenance of treatment gains over one year post-treatment. The sample included 127 children (53% female) and their parents. With regard to ethnicity, 89% of the sample described themselves as non-Hispanic, 5% Hispanic/Latino, and 6% did not endorse a category. In terms of race, the sample was predominantly (91%) White. Because the rationale and methods of the multi-site RCT have been well established, we emphasize here the methodological aspects of the study that were tailored to meet the developmental needs of young children with OCD. Aspects that are highlighted include: choice of control group, inclusion/exclusion criteria, assessment/measurement issues, treatment adaptations, training, and recruitment.